Proprotein Convertase Inhibition Results in Decreased Ski Proliferation, Tumorigenesis, and Metastasis - Daniel E. Bassi; Jirong Zhang; Jonathan Cenna; Samuel Litwin; Edna Cukierman; Andres J.P. Klein-Szanto (Neoplasia: An International Journal for Oncology Research, 2010)
PACE4 is a proprotein convertase (PC) responsible for cleaving and activating proteins that contribute to enhance tumor progression. PACE4 overexpression significantly increased the susceptibility to carcinogenesis, leading to enhanced tumor cell proliferation and premature degradation of the basement membrane. In the present study, we sought to evaluate a novel approach to retard skin tumor progression based on the inhibition of PACE4. We used decanoyl-RVKR-chloromethylketone (CMK), a small-molecule PC inhibitor, for in vitro and in vivo experiments. We found that CMK-dependent blockage of PACE4 activity in skin squamous cell carcinoma cell lines resulted in impaired insulin-like growth factor 1 receptor maturation, diminished its intrinsic tyrosine dnase activity, and decreased tumor cell proliferation. Two-stage skin chemical carcinogenesis experiments, together with topical applications of CMK, demonstrated that this PC inhibitor markedly reduced tumor incidence, tumor multiplicity, and metastasis, pointing to a significant delay in tumor progression in wild-type and PACE4 transgenic mice. These results identify PACE4, together with other PCs, as suitable targets to slow down or block tumor progression, suggesting that PC inhibition is a potential approach for therapy for solid tumors.